(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
As a social institution, the family has continuously evolved. Alterations have been made to bothits structure and its functions. The family in India, like in many traditional communities, has traditionallybeen the hub of community and economic activity and the major provider of survival necessities for itsmembers. Two hundred kids between the ages of 9 and 12 participated in the survey. Respondents fromboth rural areas and major cities were separated. The family structure in India saw major changes in thetwentieth century due to the rising commercialization of the economy and the building of the modernstate’s infrastructure.